Holistic Pain Management in Pregnancy What RNs, APRNs, Midwives and Mental Health Professionals Need to Know - Mallick-Searle, Theresa; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book presents a patient centric, holistic view and management strategy for registered nurses, advanced practice nurses and midwives to care for the pregnant female, including considerations in pregnancy planning. There is a significant gap in information about holistic care and nursing considerations of the pregnant female with regards to pain management, which this book fills. It develops on the preparation before pregnancy, as nutrition or exercise, on behavioural management of pain with the impact of anxiety and different therapies. The book examines the musculoskeletal pain, the headache and fibromyalgia occurring during pregnancy. It also informs on the nutraceuticals in pregnancy, the use of opioids and of nerve blocks. This book finally explores complementary treatments during pregnancy. Case-studies are presented for improved understanding and to provide a real-world perspective. This book, written by nursing and psychology experts in their fields of specialty practice, will appeal to nurses and midwives working with pregnant women or planning to have a baby.
Chapter 1. Introduction -- Chapter 2.Background -- Chapter 3. In preparation for pregnancy -- Chapter 4. Musculoskeletal Pain during pregnancy -- Chapter 5. Headache/migraine during pregnancy -- Chapter 6. Fibromyalgia/generalized body pain during pregnancy -- Chapter 7. Nutraceuticals in pregnancy -- Chapter 8. Opioids in pregnancy (outside OUD) -- Chapter 9. Use of nerve blocks in pregnancy -- Chapter 10. Complementary treatments in pregnancy -- Chapter 11. Behavioural management in pregnancy -- Chapter 12. Additional Case-studies.
Keywords: Nursing; Pain medicine; Midwifery; Nursing; Pain Medicine; Midwifery; Pregnancy Complications -- therapy; Pain Management -- methods; Holistic Health